2011
DOI: 10.1111/j.1464-410x.2011.10696.x
|View full text |Cite
|
Sign up to set email alerts
|

Male flexible cystoscopy: does waiting after insertion of topical anaesthetic lubricant improve patient comfort?

Abstract: What ' s known on the subject? and What does the study add? Flexible cystoscopy is commonly performed. Several studies show that topical anaesthetic lubricant reduces patient discomfort, particularly with long lubricant retention times (15 -25 min). No studies have specifi cally addressed whether a short, clinically manageable retention time provides any benefi t over immediate cystoscopy.Our study demonstrates that delay by a 3-min interval provides no benefi t to patients and a more expedient approach can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Furthermore, this time delay could increase the anxiety levels before the procedure. Other studies have failed in demonstrating the benefit of waiting a short and clinically manageable time delay (3-15 min) between the instillation of lidocaine gel and the insertion of the cystoscope when comparing with plain lubrication [2,4,6,10]. For that reason, we considered leaving the anesthetic gel for 2 min and not longer than that (<15 min) would not make any difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this time delay could increase the anxiety levels before the procedure. Other studies have failed in demonstrating the benefit of waiting a short and clinically manageable time delay (3-15 min) between the instillation of lidocaine gel and the insertion of the cystoscope when comparing with plain lubrication [2,4,6,10]. For that reason, we considered leaving the anesthetic gel for 2 min and not longer than that (<15 min) would not make any difference.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have shown that intraurethral anesthetic lubricant reduces pain compared with plain lubrication [2], others have failed in demonstrating any benefit in patient comfort [3]. Furthermore, there is no benefit from waiting a short time between the instillation of lidocaine gel and the insertion of the cystoscope [4]. It has been suggested that the gel bolus could increase pain due to the distension of the urethra and the sphincter, and that local anesthetic agents could cause pain in itself due to its chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…In their meta-analysis, Patel et al (8) also agreed, stating that there is no statistically significant difference in the efficacy of pain control between lidocaine gel and plain gel lubrication in men during flexible cystoscopy. Losco et al (9) considered the delaying of cystoscope insertion for few minutes in order to enhance efficacy of topical intraurethral lidocaine in pain reduction to be futile.…”
Section: Discussionmentioning
confidence: 99%
“…9 On the contrary, and in reference to flexible cystoscopy, some studies have demonstrated no reduction in pain relief when using topical anesthetics for short periods of time. 6 Nevertheless, others conclude that there is an improvement with long periods of intraurethral anesthetic lubricant retention. 5 In relation to long retention times, the study of Choong et al concluded that a period of 15 minutes produced a significant decrease in pain.…”
Section: Discussionmentioning
confidence: 99%
“…5 Moreover, time under 3 minutes appears not to be useful for this purpose. 6 Reviewing the information displayed in the monograph of the lubricant with a local anesthetic Cathejell 12.5 g (used in this study); anesthesia is achieved within 5 minutes, following topical application. 7 This study aims to determine whether a short, clinically manageable 5-minute time delay, between lubrication and insertion of the cystoscope versus immediate insertion, reduces discomfort in male patients undergoing flexible cystoscopy.…”
Section: Introductionmentioning
confidence: 99%